ProCare Trial: a phase II randomized controlled trial of shared care for follow‐up of men with prostate cancer. (29th August 2016) - Emery, Jon D.; Jefford, Michael; King, Madeleine; Hayne, Dickon; Martin, Andrew; Doorey, Juanita; Hyatt, Amelia; Habgood, Emily; Lim, Tee; Hawks, Cynthia; Pirotta, Marie; Trevena, Lyndal; et al.
Abstract : Objectives: To test the feasibility and efficacy of a multifaceted model of shared care for men after completion of treatment for prostate cancer. Patients and Methods: Men who had completed treatment for low‐ to moderate‐risk prostate cancer within the previous 8 weeks were eligible. Participants were randomized to usual care or shared care. Shared care entailed substituting two hospital visits with three visits in primary care, a survivorship care plan, recall and reminders, and screening for distress and unmet needs. Outcome measures included psychological distress, prostate cancer‐specific quality of life, satisfaction and preferences for care and healthcare resource use. Results: A total of 88 men were randomized (shared care n = 45; usual care n = 43). There were no clinically important or statistically significant differences between groups with regard to distress, prostate cancer‐specific quality of life or satisfaction with care. At the end of the trial, men in the intervention group were significantly more likely to prefer a shared care model to hospital follow‐up than those in the control group (intervention 63% vs control 24%; P <0.001). There was high compliance with prostate‐specific antigen monitoring in both groups. The shared care model was cheaper than usual care (shared care AUS1411; usual care AUS1728; difference AUS323 [plausible range AUS91–554]). Conclusion: Well‐structured shared care for men with low‐ to moderate‐risk prostate cancer is feasible and appears to produce clinically similar outcomes to those of standard care, at a lower cost.